Predictors of early death and clinical features in newly diagnosed patients with low-intermediate risk acute promyelocytic leukemia - Wen, Jingjing; Xu, Fang; Zhou, Qiaolin; Shi, Lin; Liu, Yiping; Yue, Jing; Zhang, Ya; Liang, Xiaogong (Frontiers in Oncology, 2022)
Background: Although most acute promyelocytic leukemia(APL) with low-intermediate risk could survive the induction treatment, early death still a big problem to have effects on overall survival in real world.This study aimed to analyze the clinical characteristics and possible predictors of early death in newly diagnosed patients with low-intermediate-risk acute promyelocytic leukemia . Methods: Sixty patients with newly diagnosed low/intermediate-risk APL admitted to Mianyang Central Hospital from January 2013 to December 2021 were retrospectively analyzed. Results: Sixty patients with a median age of 46 years (range, 17-75 years) were included. Fourteen patients (23.3%) were in low-risk group, and 46 patients (76.7%) were in intermediate-risk group. Fourteen patients (23.3%) died during induction treatment. Five patients died of hemorrhage, 5 of severe infection and 4 of differentiation syndrome. Multivariate analysis showed that HGB <65g/L at diagnosis (OR=38.474, 95%CI: 2.648~558.923, P=0.008) during induction treatment was an independent risk factors for early death in low- intermediate risk APL patients. In survival group, all patients achieved complete remission, the time to achieve remission was 25.87±5.02 days, the average ATO dosage was 0.16±0.03 mg/kg/day. In univariate analysis, there was no statistically significant difference in time span for remission when ATO dosage was in the 0.11~0.16mg/kg/day range. Compared with patients with low-risk APL, those with intermediate-risk APL had higher white blood cell counts (at diagnosis, day 3, day 5 and peak), higher level of lactate dehydrogenase, higher percentage of bone marrow promyelocytes, more platelet transfusions during treatment, and more early deaths (P<0.05). The overall survival of intermediate-risk APL patients seemed worse than those with low-risk APL (c=5.033, P =0.025). Conclusions: In patients with low-intermediate risk APL, HGB <65g/L at diagnosis was an independent risk factors for early death. Remission could still be achieved at low-dose ATO without affecting the required time for low-intermediate risk APL patients. Differences in clinical characteristics were found between low-risk and intermediate-risk APL. The intermediate-risk group had higher early mortality risk than the low-risk group.